Effects of weaning weight on reproductive performance in beef heifers - Sprott, L.R.; Corah, L.R.; Kiracofe, G.H. (Kansas State University. Agricultural Experiment Station, 2011)
Fertility during the first two breeding seasons was not affected by the dam's weaning weight, but lightest heifers at weaning reached puberty later, had smaller pelvic areas at calving, more difficult deliveries, had more calves die, and weaned a smaller percentage of their calves.
Keywords: Beef; Weaning weight; Reproductive performance; Heifers